2020
DOI: 10.1016/j.cognition.2019.104075
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic rejection templates in visual working memory

Abstract: Our interactions with the visual world are guided by attention and visual working memory. Things that we look for and those we ignore are stored as templates that reflect our goals and the tasks at hand. The nature of such templates has been widely debated. A recent proposal is that these templates can be thought of as probabilistic representations of task-relevant features. Crucially, such probabilistic templates should accurately reflect feature probabilities in the environment. Here we ask whether observers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 36 publications
6
29
0
1
Order By: Relevance
“…www.nature.com/scientificreports/ Implicit assessment. Overall, observers had a remarkably detailed representation of the distractor distribution, well above the mean and variance only, in stark contrast with typical findings on ensemble perception, but importantly corroborating previous findings of implicit encoding of distractor distributions 20,[24][25][26][27] . Figure 4A plots the RT curves for the implicit condition and as previously found, the RTs for the current target as a function of the previous distractor distribution (CT-PD) reflect the Gaussian distribution shape.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…www.nature.com/scientificreports/ Implicit assessment. Overall, observers had a remarkably detailed representation of the distractor distribution, well above the mean and variance only, in stark contrast with typical findings on ensemble perception, but importantly corroborating previous findings of implicit encoding of distractor distributions 20,[24][25][26][27] . Figure 4A plots the RT curves for the implicit condition and as previously found, the RTs for the current target as a function of the previous distractor distribution (CT-PD) reflect the Gaussian distribution shape.…”
Section: Resultssupporting
confidence: 85%
“…Search times on these test trials are analyzed as a function of the distance in feature space between the current target (that is searched for) and the previously learned distractor distribution mean (hereafter named CT-PD, current target-previous distractors distance). Previous results 20,[24][25][26][27] have shown that the RT curve should follow the shape of the encoded distribution, providing evidence that detailed distribution characteristics are encoded.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…An ideal observer utilizing the knowledge of previous distractors would respond slower when a test target is similar to previous distractors with the degree of slowing monotonically related to the shape of distractor distributions. This is indeed what we found in our previous studies (Chetverikov et al, 2016(Chetverikov et al, , 2017a(Chetverikov et al, , 2020. We refer to the test target position in the feature space as the current-target to previous distractor-distance (CT-PD).…”
Section: Procedures and Stimulisupporting
confidence: 83%
“…These explicit judgments on statistical parameters of a feature distribution might have limited power in revealing how accurately feature distributions in an ensemble are encoded by the visual system. Recently, Chetverikov, Campana, and Kristjánsson (2016 , 2017a , 2017b , 2017c , 2020 ) used a novel method to demonstrate that observers can encode the probability density function underlying the distractor distribution in an odd-one-out visual search task for orientation (2016, 2017a) and color (2017b). Instead of using explicit judgments of distribution statistics, they measured observers’ visual search times varying target similarity to previously learned distractors, which revealed observers’ expectations of distractor feature distributions.…”
Section: Introductionmentioning
confidence: 99%